ANALISIS DAYA SAING DAN FAKTOR YANG MEMPENGARUHI EKSPOR BATUBARA INDONESIA KE LIMA NEGARA TUJUAN UTAMA - Girsang, Ade Christy Yolanda Br; Bendesa, I Komang Gde (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 12 (2022): Vol.11.12. DESEMBER 2022[4234-4463]DO - 10.24843/EEP.2022.v11.i12.p02, 2022)
Indonesia one of largest countries that play a role in world coal exports. The purpose this study analyze competitiveness that affects Indonesia's coal exports to the five main destination countries in 2013-2020. The data used panel data which is a combination of time series and cross section data. To analyze the comparative competitiveness of Indonesian coal commodities in the five destination countries, the RCA (Revealed Comparative Advantage) method is used and competitively, the ECI method is used. The RCA and ECI values obtained for the five destination countries show that Indonesian coal exports have strong competitiveness. Based on the results of the study, partially production has a positive and insignificant effect, prices have a positive and significant effect on Indonesian coal exports, while the exchange rate has a negative and significant effect on Indonesian coal exports to the five main destination countries. Keywords: Coal Exports, RCA, Production, Exchange Rates, Prices